Economic stratification and living conditions in the canadian arctic - Duhaime, Gérard; Édouard, Roberson; Bernard, Nick (Nordic Council of Ministers, 2024)
This chapter discusses the stratification of contemporary Inuit societies in Canada. An analysis of total individual and household income enabled the authors to determine income distribution among the adult Inuit population across different strata. This analysis made it possible to go beyond merely describing income distribution and to observe a significant but weak relationship between economic stratification and the living conditions thus examined (schooling level, civic participation, social support, satisfaction in relation to certain aspects of community life, and subjective well-being). It also showed that the criteria of social differentiation include aside from various sources of income - access to and availability of social support, participation in community life, satisfaction, and wellbeing. All in all, economic stratification appears, all things considered, to have a limited impact on the core aspects of life for the Canadian Arctic Inuit. Other processes are thought to interact with stratification to produce and materialize the cohesion required for the maintenance and development of local communities - such as, for example, the strength of social networks, the presence of family, or the principle of reciprocity.